Pengaruh Program KUR dan BLT terhadap Kinerja UMKM dengan Strategi Diferensiasi sebagai Variabel Mediasi - Irma Suryani; Maria Rio Rita (Jurnal Manajemen dan Keuangan, 2023)
This study aims to examine the impact of the Kredit Usaha Rakyat (KUR) and Bantuan Langsung Tunai (BLT) programs on the performance of MSMEs through differentiating mediation strategies. This study involved SMEs in Salatiga City using a purposive sampling method to purchase samples. Data is processed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The reported findings are that the KUR and BLT programs have a significant positive effect on the differentiation strategy and also on the performance of MSMEs. It is also proven that differences in strategy mediate the effect of the KUR and BLT programs on MSME performance. This can be a reference for MSME actors to increase capital in a business by wisely using the KUR and/or BLT programs to support the implementation of a differentiation strategy to improve operations.